Software Reengineering: New Approach to Software Development (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
Programs are often reengineered for better maintainability in the way to make new softwares with the help of programs re-engineering..Program reengineering is not a simple task because code reengineer or code reengineer is such a difficult and a challenging task. In software reengineering the existing system is reengineer or refined to produce the new software. In this research paper we try to describe the activities that are helpful in reengineer the existing software or program to produce the new one.